Trades access common core. Line D. Organizational skills; Competency D-1 Solve Trades Mathematical Problems - Lidstone, Rod; Camosun College; British Columbia. Ministry of Technolgy, Innovation and Citizens' Services; BC Open Textbook Project; BCcampus (Ministry of Technology, Innovation and Citizens' Services, 2015)
"Essential skills are used in every job to varying degrees and at different levels of complexity. They provide the foundation for learning all other skills and enable people to evolve in their jobs and adapt to changes in the workplace. The following list of lines and competencies was generated with the goal of creating an entry-level trades training resource, while still offering the flexibility for lines to be used as stand-alone books"--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"Copyright Camosun College"--P. 2.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Mathematics -- Textbooks; Geometry -- Textbooks; Electronic books